Twenty Years of Building International Relations on the Territory of the CIS: the Polish Perspective - A. Kovalchuk (Vestnik MGIMO-Universiteta, 2012)
The article presents the main issues of international relations in the post-soviet area since the collapse of the Soviet Union, perceived by Polish political scientists as critical to the modern structure of relations in the region. Russia's foreign policy towards the CIS countries is the main aspects of discussion. The following issues relate to the bilateral relations with Russia, and domestic situation of former Soviet countries, as well as the institutionalization of cooperation within the CIS.